2017
DOI: 10.1016/j.scriptamat.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the three-dimensional damage and stress redistribution mechanisms of braided SiC/SiC composites by in situ volumetric digital image correlation

Abstract: Coupled in situ micro-X-ray computed tomography and volumetric digital image correlation (V-DIC) strain measurements of expanding plug tests revealed the three-dimensional, microstructure-dependent mechanisms behind strain localization, damage initiation and stress redistribution in braided SiC/SiC composites. Hoop strain varied significantly through the composite thickness and was highest at regions of tow crossover; at higher loads, tow fracture initiated at these locations, and sample rupture propagated axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Furthermore, SiC CMCs have been rigorously tested within the aerospace community, where high temperature properties and corrosion resistance are critical requirements of many materials . In a reactor environment, the onset of matrix microcracking coupled with the loss of cladding hermeticity can allow the escape of radiative fuel and gases with potentially disastrous consequences, even though the cladding may still possess full load‐bearing capabilities . In order for these CMCs to be accepted by the stringent nuclear community, they must be exhaustively evaluated and examined through a suite of investigations to elucidate their full failure behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SiC CMCs have been rigorously tested within the aerospace community, where high temperature properties and corrosion resistance are critical requirements of many materials . In a reactor environment, the onset of matrix microcracking coupled with the loss of cladding hermeticity can allow the escape of radiative fuel and gases with potentially disastrous consequences, even though the cladding may still possess full load‐bearing capabilities . In order for these CMCs to be accepted by the stringent nuclear community, they must be exhaustively evaluated and examined through a suite of investigations to elucidate their full failure behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8]). The damage initiation of CMCs is related to the appearance of cracks, which is commonly considered to be induced by stress concentration around sharp edges of pores inside the material [9][10][11]. Due to the multiscale nature of the CMC microstructures, pores are usually classified into two groups: micropores located inside the fiber tows and macropores located among fiber tows.…”
Section: Introductionmentioning
confidence: 99%
“…In situ X-ray micro-computed tomography (µCT) testing is a powerful tool to experimentally observe cracks within a material, and provides volume information about both the microstructure and the microcrack networks [12,13]. Crack evolution, such as growth path, can be studied with respect to the 3D microstructure [10,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experiments and models have demonstrated that the stochastic positioning of tows causes stress localization and alters damage and failure propagation . In fact, recent high‐resolution, in situ experiments have suggested that irregular tow spacing in chemical vapor infiltration densified, braided CMCs is correlated with the location of composite failure …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In fact, recent high-resolution, in situ experiments have suggested that irregular tow spacing in chemical vapor infiltration densified, braided CMCs is correlated with the location of composite failure. 6 Given that the arrangement of tows within CMCs can predict some of the statistical variation in observed mechanical properties, there is great interest in understanding the stochastic properties of such composite architectures. This is particularly valuable for nuclear energy applications, where the hermeticity of fuel cladding could be influenced by variation in tow spacing.…”
Section: Introductionmentioning
confidence: 99%